2018
DOI: 10.1021/acscatal.8b02815
|View full text |Cite
|
Sign up to set email alerts
|

Acyl and Decarbonylative Suzuki Coupling of N-Acetyl Amides: Electronic Tuning of Twisted, Acyclic Amides in Catalytic Carbon–Nitrogen Bond Cleavage

Abstract: We report the Pd-catalyzed acyl and the Ni-catalyzed biaryl Suzuki–Miyaura cross-coupling of N-acetyl-amides with arylboronic acids by selective N–C­(O) cleavage. Activation of the amide bond by N-acylation provides electronically destabilized, acyclic, nonplanar amide, which readily undergoes cross-coupling with a wide range of boronic acids to produce biaryl ketones or biaryls in a highly efficient manner. Most crucially, the presented results introduce N-acetyl-amides as reactive acyclic amides in the emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(43 citation statements)
references
References 85 publications
1
42
0
Order By: Relevance
“…More recently, we have reported "mono-twisted" N-Ac-amides as highly reactive acyclic amides in acyl Suzuki cross-coupling (Scheme 23E) [81]. In this work, it was demonstrated that catalyst selection dictates an acyl or decarbonylative mechanism.…”
Section: Suzuki Cross-coupling Of Amidesmentioning
confidence: 82%
“…More recently, we have reported "mono-twisted" N-Ac-amides as highly reactive acyclic amides in acyl Suzuki cross-coupling (Scheme 23E) [81]. In this work, it was demonstrated that catalyst selection dictates an acyl or decarbonylative mechanism.…”
Section: Suzuki Cross-coupling Of Amidesmentioning
confidence: 82%
“…[65] In 2018, Szostak and co-workers reported ap alladium-catalyzed cross-coupling reaction of N-Ph,N-acyl amides with arylboronic acids and an ickel-catalyzed decarbonylative Suzuki-Miyaura cross-coupling reactiono fN-acetyl amides with arylboronic acids through NÀCa ctivation (Scheme 37). [75] Common planar amides were converted into twisted (acyclic) amides, Scheme33. Nickel-catalyzed cross-coupling reaction of aryl halides with amidesthrough NÀCa ctivation.…”
Section: Cross-coupling and Other Reactionsmentioning
confidence: 99%
“…To date, a wide range of amides and amide-based reagents, including the most reactive N-acyl-glutarimides [13] as well as anilides [14], N-Boc-carbamates [15], N-Ts-sulfonamides [16], N, N-di-Boc amides [17], N-acyl-saccharins [18,19], N-Ms-sulfonamides [20], N-acyl-pyrroles [21], N-Me-pyrimidines [22], N-acyl-succinimides [23][24][25], and N-Ac-amides [26] have been successfully engaged as electrophilic cross-coupling partners by N-C activation. In all examples described to date, the reactivity has been controlled by a ground-state destabilization mechanism of the amide bond [12].…”
Section: Introductionmentioning
confidence: 99%